Is CT adequate to assess for malignant cord compression?. (September 2015) - Catherine, Gemma; MacLeod, Nicholas; Sheridan, Simon
Abstract : Purpose: At the Beatson Oncology Centre, Glasgow there is a weekend emergency spinal cord compression service providing two magnetic resonance imaging (MRI) slots for patients throughout the West of Scotland. Out-of-hours MRI is not available at local hospitals. Patients are transferred to the Beatson for emergency MRI and emergency treatment with radiotherapy if required. The aim of this study is to identify the role of computed tomography (CT) as a screening tool for patients prior to transfer, to avoid unnecessary transfers. Methods and materials: Patients who had undergone emergency weekend MRI scans for malignant spinal cord compression were identified between January 2014 and 2015. The radiology information system (RIS) was used to review previous imaging history and identify relevant contemporaneous CT imaging which was then reviewed. Results: The study identified 27 patients as having a weekend MRI scan at the Beatson for possible malignant spinal cord compression. Of these, 13 had a positive MRI scan demonstrating malignant spinal cord compression. Of these 13 patients, 12 patients had a contemporaneous CT scan. In all 12 cases, CT readily identified the level of cord compression. Conclusion: CT is available at all local sites and readily demonstrates the level of malignant spinal cord compression. It has a role in identifying patients who would benefit from transfer to the Beatson for further imaging with MRI. This will in turn reduce the number of patients undergoing unnecessary transfer from their local hospitals.